Role of thioredoxin-interacting protein in mediating endothelial dysfunction in hypertension - Wang, Ruiyu; Guo, Yongzheng; Li, Lingjiao; Luo, Minghao; Peng, Linqian; Lv, Dingyi; Cheng, Zhe; Xue, Qian; Wang, Liang; Huang, Jing (Genes & diseases, 2022)
Excessive oxidative stress is a major causative factor of endothelial dysfunction in hypertension. As an endogenous pro-oxidant, thioredoxin-interacting protein (TXNIP) contributes to oxidative damage in various tissues. The present study aimed to investigate the role of TXNIP in mediating endothelial dysfunction in hypertension. In vivo, an experimental model of acquired hypertension was established with two-kidney, one-clip (2K1C) surgery. The expression of TXNIP in the vascular endothelial cells of multiple vessels was significantly increased in hypertensive rats compared with sham-operated rats. Resveratrol, a TXNIP inhibitor, suppressed vascular oxidative damage and increased the expression and activity of eNOS in the aorta of hypertensive rats. Notably, impaired endothelium-dependent vasodilation was effectively improved by TXNIP inhibition in hypertensive rats. In vitro, we observed that Ang II increased the expression of TXNIP in primary human aortic endothelial cells (HAECs) and that TXNIP knockdown by RNA interference alleviated cellular oxidative stress damage and mitigated the impaired eNOS activation and intracellular nitric oxide (NO) production observed in Ang II-treated HAECs. However, inhibiting thioredoxin (TRX) with PX-12 completely blunted the protective effect of silencing TXNIP. In addition, TXNIP knockdown facilitated TRX expression and promoted TRX nuclear translocation to further activate AP1 and REF1. TRX overexpression exhibited favorable effects on eNOS/NO homeostasis in Ang II-treated HAECs. Thus, TXNIP contributes to oxidative stress and endothelial dysfunction in hypertension, and these effects are dependent on the antioxidant capacity of TRX, suggesting that targeting TXNIP may be a novel strategy for antihypertensive therapy.